Integrating forage and feed advisory into iSAT for climate resilient livestock in Senegal - Joseph, Jacob Emanuel; Edorh, Theophile; Folorunso, Akinseye; Worou, Nadine; Houessionon, Prosper; Whitbread, M. Anthony (International Livestock Research Institute, 2025)
Livestock production is a cornerstone of Senegal’s rural economy, yet it faces persistent challenges of feed scarcity, low forage quality, and increasing climate variability. To address these constraints, the International Livestock Research Institute (ILRI) and partners convened a two-day workshop (June 3–4, 2025, Mamelles, Senegal) dedicated to advancing the iSAT (Intelligent Agricultural System Advisory Tool) platform for forage and livestock feed advisory services. The workshop brought together 16 experts in forage agronomy, animal nutrition, climatology, and data systems in a participatory process to co-design and validate practical advisory tools. Key outputs included validated seasonal calendars for priority forage species, decision trees for forage management that integrate climate risk considerations, and initial protocols for balanced feed formulation. In addition, participants explored market linkage models and established a WhatsApp group to sustain collaboration and validate advisory messages beyond the event. These results represent a significant step toward extending iSAT’s proven crop advisory services into livestock systems, thereby enhancing climate resilience, improving productivity, and strengthening the economic sustainability of agropastoral households in Senegal.